COVID-19 Related Myocarditis and Myositis in a Patient with Undiagnosed Antisynthetase Syndrome - Daniel Duda-Seiman; Nilima Rajpal Kundnani; Daniela Dugaci; Dana Emilia Man; Dana Velimirovici; Simona Ruxanda Dragan (Biomedicines, 2022)
Background: The clinical presentation of SARS-CoV-2 varies from patient to patient. The most common findings noted were respiratory tract infections, of different severity grades. In some cases, multi-organ damage was noted. Due to its high potential for causing severe systemic inflammation such as myositis and myocarditis, patients should be properly investigated, which carries high chances of SARS-CoV-2 being easily missed if not investigated on time and which can result in more fatal outcomes. Case report: We present a case of COVID-19 infection in a non-vaccinated male patient, who presented to our clinic with no symptoms of respiratory involvement but with severe muscle aches. Cardiac markers and procalcitonin levels were high, and concentric hypertrophy of the left ventricle, severe hypokinesia of the interventricular septum and of the antero-lateral wall, hypokinesia of the inferior and posterior wall and an ejection fraction of the left ventricle being around 34% was noted. Coronary angiography showed no lesions. Corticosteroids and antibiotics were instituted which showed improvement. A possible link to an autoimmune process was suspected, due to the presence of anti-PL-7 antibody, suggesting an antisynthetase syndrome. Conclusion: Each and every patient should be thoroughly investigated, and presently little is known in regards to this virus. Studies focusing on possible relationships between the COVID-19 and autoimmune disease can help to potentially generate better outcomes.